Birth Order and Voter Turnout. Issue 1 (10th January 2022) - Bratsberg, Bernt; Dawes, Christopher T.; Kotsadam, Andreas; Lindgren, Karl-Oskar; Öhrvall, Richard; Oskarsson, Sven; Raaum, Oddbjørn
Abstract: Previous studies have stressed the role of a child's family environment for future political participation. This field of research has, however, overlooked that children within the same family have different experiences depending on their birth order. First-borns spend their first years of life without having to compete over their parents' attention and resources, while their younger siblings are born into potential rivalry. We examine differences in turnout depending on birth order, using unique population-wide individual level register data from Sweden and Norway that enables precise within-family estimates. We consistently find that higher birth order entails lower turnout, and that the turnout differential with respect to birth order is stronger when turnout is lower. The link between birth order and turnout holds when we use data from four other, non-Nordic countries. This birth order effect appears to be partly mediated by socio-economic position and attitudinal predispositions.